The efficacy and safety of gemcitabine-based induction chemotherapy for locally advanced nasopharyngeal carcinoma treated with concurrent chemoradiation: A meta-analysis. Issue 14 (9th April 2021) - Fei, Qian; Chen, Han-Bo; Zhang, Chun-Mei; Xu, Jia-Jun; He, Xia; Chen, Song-Wang
Abstract: Objectives: To assess the efficacy and toxicity of gemcitabine-based induction chemotherapy followed by concurrent chemoradiotherapy (CCRT) in locally advanced nasopharyngeal carcinoma (LA-NPC). Methods: Both observational studies (OBS) and randomized controlled trials (RCT) were included in the meta-analysis. Systematic online searches were conducted in Web of Sciences, PubMed, Embase, meeting proceedings and ClinicalTrials.gov from the inception to May 25, 2020. The primary endpoint of interest was overall survival. Results: five OBSs and 2 RCTs including 1680 patients were incorporated in the analysis. The evidence from the RCTs showed that adding gemcitabine-based induction chemotherapy to CCRT significantly improved progression free survival (hazard ratio (HR): 0.60, 95% confidence interval (CI): 0.40–0.88; P = .010; chi square P = .25; I 2 = 24%) and overall survival (HR: 0.47; 95% CI: 0.28–0.80; P = 0.005; chi square P = .49, I 2 = 0%) and was related to a higher risk of hematological toxicities. Furthermore, based on the data of OBSs, overall survival (HR: 0.52; 95% CI: 0.31–0.88; P = .02; chi square P = .37, I 2 = 6%) was significantly improved in patients treated with gemcitabine-based induction chemotherapy compared to those treated with taxane-based induction chemotherapy. However, the progression free survival (HR: 0.67; 95% CI: 0.45–1.01; P = .06; chi square P = .74; I 2 = 0%) showed no significant difference. Conclusions: For LA-NPC patients, adding gemcitabine-based induction chemotherapy to CCRT significantly improved overall survival and progression free survival with a higher risk of hematological toxicities when compared to CCRT alone. Also, gemcitabine-based regimen could be used as an alternative induction chemotherapy regimen to taxane-based regimen in the treatment of LA-NPC.